2021
DOI: 10.3390/cancers13051088
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Term Audit of a National Peritoneal Surface Malignancy Program Implementation in a Low Middle Income Country: The Moroccan Experience

Abstract: Implementing a multimodal management of peritoneal surface malignancies is a steep and complex process, especially as complete cytoreductive surgery (CRS) is the backbone and the major prognostic factor for hyperthermic intraperitoneal chemotherapy (HIPEC) procedures. The implementation of such a program is a challenging process, particularly in low-middle income (LMIC) countries where ressource restrictions may represent a major hurdle to HIPEC appliances acquisition. Herein is the first audit of the implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…In resource restricted contexts such as in the North African region, the prioritization and indications for the curative treatment may also face the constraints of limited critical care and surgical resources management and expertise (22,(38)(39)(40)(41). In fact, while only 26.2% of our respondents reported having access to HIPEC, a similar study on practice patterns in PC from the USA identified 65.8% of its participants as having easy access to a HIPEC and CRS specialists, with 42.7% being in the same hospital (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In resource restricted contexts such as in the North African region, the prioritization and indications for the curative treatment may also face the constraints of limited critical care and surgical resources management and expertise (22,(38)(39)(40)(41). In fact, while only 26.2% of our respondents reported having access to HIPEC, a similar study on practice patterns in PC from the USA identified 65.8% of its participants as having easy access to a HIPEC and CRS specialists, with 42.7% being in the same hospital (33).…”
Section: Discussionmentioning
confidence: 99%
“…As such, we choose to include the private sector in our analysis, which indeed demonstrated that the significantly higher availability in the private sector of some therapies such as pressurized intraperitoneal chemotherapy and low dose radiotherapy didn't necessarily yield a higher level of satisfaction in the available treatment modalities. Regardless of the activity sector, the level of expertise is considered a better reflection ( 22 ), especially as the PSM treatment learning curve can be steep and complex ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes, hysterectomy, bilateral salpingo-oophorectomy, omentectomy as well as additional procedures such as peritonectomies ( 9 ), bowel resections, diaphragm peritonectomy with or without segmental full-thickness diaphragm resection, splenectomy with or without distal pancreatectomy, segmental liver resection, cholecystectomy, partial stomach resection, and partial bladder/ureteral resection ( 10 ). Postoperative residual disease was shown to be a major prognostic factor of overall survival ( 11 13 ), hence the necessity of surgery to be complete. In fact, surgery used to be qualified as “optimal” in reference to a residual tumour of less than 1 cm, but this is not the goal anymore.…”
Section: Introductionmentioning
confidence: 99%
“…In our experience, objectively and easily grading the extent of surgery through the BESt MAnagement Technique for HIpec score has allowed for better communication in the MDT, which has been reflected in clinical and postoperative results through better patient preparation and anticipation of the procedures. 5 The Besmathi score is a four scale tool that is categorized as follows:…”
mentioning
confidence: 99%